Phytosynthesis and Characterization of Silver Nanoparticles from Antigonon leptopus: Assessment of Antibacterial and Cytotoxic Properties - Marisol Gastelum-Cabrera; Pablo Mendez-Pfeiffer; Manuel G. Ballesteros-Monrreal; Brenda Velasco-Rodríguez; Patricia D. Martínez-Flores; Sergio Silva-Bea; Vicente Domínguez-Arca; Gerardo Prieto; Silvia Barbosa; Ana Otero; Pablo Taboada; Josué Juárez (Pharmaceutics)
Background: Silver nanoparticles (AgNPs) show promises as antimicrobial biomaterials with use for combating multidrug-resistant microorganisms, and they are widely used in healthcare, medicine, and food industries. However, traditional physicochemical synthesis methods often require harsh conditions and toxic reagents, generating harmful waste. The synthesis of AgNPs using plant-derived bioactive compounds offers an eco-friendly alternative to conventional methods. Methods: In this study, a bio-green approach was employed to synthesize AgNPs using ethanolic extracts from Antigonon leptopus leaves (EXT-AL). The synthesis was optimized under different pH conditions (5.5, 8.0, 10.0) and EXT-AL concentrations (10–200 μg/mL). Antibacterial activity was evaluated against Escherichia coli and Staphylococcus aureus, and cytotoxicity was assessed in HeLa, CaCo-2, T731-GFP, and HaCaT cell lines. Results: UV-Vis spectroscopy confirmed nanoparticle formation, with a surface plasmon resonance peak at 410 nm. Alkaline conditions (pH 10.0) favored the formation of smaller, spherical AgNPs. Characterization by DLS, TEM, and AFM revealed uniform nanoparticles with a hydrodynamic diameter of 93.48 ± 1.88 nm and a zeta potential of −37.80 ± 1.28 mV. The AgNPs remained stable in Milli-Q water but tended to aggregate in PBS, DMEM, and MHB media. Antibacterial assays demonstrated significant bactericidal activity against Escherichia coli and Staphylococcus aureus at 3.9 μg/mL (Ag⁺ equivalent). Cytotoxicity tests showed no toxicity to HeLa, T731-GFP, CaCo-2, or HaCaT cells at concentrations ≥ 7.8 μg/mL after 24 h. Conclusions: These findings highlight Antigonon leptopus extract as a sustainable and cost-effective resource for AgNPs synthesis, with strong antimicrobial properties and potential biomedical applications.